The marine isotope stage 1 to 5 cryptotephra record of Tenaghi Philippon, Greece: Towards a detailed tephrostratigraphic framework for the Eastern Mediterranean region - Tomlinson, Emma; Wulf, Sabine; Hardiman, Mark; Staff, Richard A.; Koutsodendris, Andreas; Appelt, Oona; Blockley, Simon P.E.; Lowe, J. John; Manning, Christina J.; Ottolini, Luisa; Schmitt, Axel K.; Smith, Victoria C.; et al. (My University, 2018)
The iconic climate archive of Tenaghi Philippon (TP), NE Greece, allows the study of short-term palaeoclimatic and environmental change throughout the past 1.3 Ma. To provide high-quality age control for detailed palaeoclimate reconstructions based on the TP archive, (crypto)tephra studies of a peat core ‘TP-2005’ have been carried out for the 0–130 ka interval. The results show that the TP basin is ideally positioned to receive tephra fall from both the Italian and Aegean Arc volcanic provinces. Two visible tephra layers, the Santorini Cape Riva/Y-2 (c. 22 ka) and the Campanian Ignimbrite (CI)/Y-5 (c. 39.8 ka) tephras, and six primary cryptotephra layers, namely the early Holocene E1 tephra from the Aeolian Islands (c. 8.3 ka), the Campanian Y-3 (c. 29 ka) and X-6 tephras (c. 109.5 ka), as well as counterpart tephras TM-18-1d (c. 40.4 ka), TM-23-11 (c. 92.4 ka) and TM-33-1a (c. 116.7 ka) from the Lago Grande di Monticchio sequence (southern Italy), were identified along with repeatedly redeposited Y-2 and CI tephra material. Bayesian modelling of the ages of seven of the primary tephra layers, 60 radiocarbon measurements and 20 palynological control points have been applied to markedly improve the chronology of the TP archive. This revised chronology constrains the age of tephra TM-18-1d to 40.90–41.66 cal ka BP (95.4% range). Several tephra layers identified in the TP record form important isochrons for correlating this archive with other terrestrial (e.g., Lago Grande di Monticchio, Sulmona Basin and Lake Ohrid) and marine (e.g., Adriatic Sea core PRAD 1-2 and Aegean Sea core LC21) palaeoclimate records in the Mediterranean region.
PUBLISHED
Keywords: Tephrochronology; Last glacial-interglacial cycle; Tenaghi philippon; Eastern Mediterranean region; Peat record; Italian volcanism; Santorini eruptions